The predicting role of perfectionism on team cohesion among Brazilian futsal athletes - José Roberto Andrade do Nascimento Junior; Gabriel Lucas Morais Freire; Adson Alves da Silva; Nathan Leonardo Gomes Costa; Leonardo de Sousa Fortes; Daniel Vicentini de Oliveira (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This cross-sectional study investigated the predicting role of perfectionism on the perception of team cohesion among futsal athletes. Methods: One hundred and forty of futsal athletes (24.8±4.9 years) were included who participated of a Brazilian Amateur Cup in 2017. The instruments were Sport Multidimensional Perfectionism Scale-2 and Group Environment Questionnaire. Data analysis was conducted through the Pearson Correlation and Multiple Regression Analysis (p < .05). Results: The data showed the following significant correlations (p < .05): Group-Integration Task (GI-T) with Organization-Personal Standards (OPS) (r = .27) and Doubts About Action (DAA) (r = -.24); Group-Integration Social (GI-S) with OPS (r = .18); Individual Attraction to Group-Task (IA-T) with OPS (r = .25); Individual Attraction to the Group-Social (IA-S) with OPS (r = .17). Multiple regression showed that OPS showed a positive association with task cohesion dimensions (GI-T and IA-T), while DAA showed a negative association with both social (GI-S and IA-S) and task (GI-T) cohesion. Further, perceived parental pressure showed positive association with GI-S. Conclusion: our findings show that perfectionistic striving could be a positive predictor of task cohesion, while perfectionistic concerns might predict negatively both social and task cohesion.